Development of emotion regulation across the first two years of college. (1st October 2020) - Park, Crystal L.; Williams, Michelle K.; Hernandez, Paul R.; Agocha, V. Bede; Lee, Sharon Y.; Carney, Lauren M.; Loomis, David
ABSTRACT: Introduction: Emotion regulation is thought to develop substantially from late adolescence into early adulthood; further, the rate of development purportedly varies based on personal and contextual characteristics. However, little research has explicitly documented this maturation in young adulthood or identified its determinants. We aimed to (1) characterize how adaptive (positive reappraisal, emotional social support‐seeking) and maladaptive (suppression, substance use coping) emotion regulation strategies changed over time and (2) predict change in each strategy based on baseline personal, social, and motivational characteristics. Methods: We followed a sample of 1578 students entering university in the northeastern United States across their first two years, assessing them four times. Results: As expected, social support‐seeking increased and suppression decreased. However, contrary to expectations, cognitive reappraisal declined over time while substance use coping increased. Women generally used more adaptive emotion regulation strategies than did men; social engagement and connection and eudaimonic well‐being were generally predictive of using more adaptive coping over time. Conclusions: Overall, students did not consistently demonstrate maturation to more adaptive emotion regulation and in fact exhibited decrements over the first two years of college. Students' baseline characteristics accounted for substantial degrees of change in emotion regulation. These findings suggest potentially fruitful directions for interventions to assist college students in developing more adaptive emotion regulation skills.